Investigating Predictive Factors of Suicidal Re-attempts in Adolescents and Young Adults After a First Suicide Attempt, a Prospective Cohort Study. Study Protocol of the SURAYA Project - Abrial, Erika; Chalancon, Benoît; Leaune, Edouard; Brunelin, Jérôme; Wallon, Martine; Moll, Frédéric; Barakat, Nadine; Hoestlandt, Benoit; Fourier, Anthony; Simon, Louis; Magnin, Charline; Hermand, Marianne; et al. (Frontiers in Psychiatry, 2022)
Abstract Introduction: Suicide is the fourth leading cause of death in youth. Previous suicide attempts are among the strongest predictors of future suicide re-attempt. However, the lack of data and understanding of suicidal re-attempt behaviors in this population makes suicide risk assessment complex and challenging in clinical practice. The primary objective of this study is to determine the rate of suicide re-attempts in youth admitted to the emergency department after a first suicide attempt. The secondary objectives are to explore the clinical, socio-demographic and biological risk factors that may be associated with re-attempted suicide in adolescents and young adults. Methods: We have developed a single-center prospective and naturalistic study that will follow a cohort of 200 young people aged 16 to 25 years admitted for a first suicide attempt to the emergency department of Lyon, France. The primary outcome measure will be the incidence rate of new suicide attempts during three months of follow-up. Secondary outcomes to investigate predictors of suicide attempts will include several sociodemographic, clinical and biological assessments: blood and hair cortisol levels, plasma pro- and mature Brain-Derived Neurotrophic Factor (BDNF) isoforms proportion, previous infection with toxoplasma gondii, and C-Reactive Protein (CRP), orosomucoid, fibrinogen, interleukin (IL)-6 inflammatory markers. Discussion: To our knowledge, the present study is the first prospective study specifically designed to assess the risk of re-attempting suicide and to investigate the multidimensional predictive factors associated with re-attempting suicide in youth after a first suicide attempt. The results of this study will provide a unique opportunity to better understand whether youth are an at-risk group for suicide re-attempts, and will help us identify predictive factors of suicide re-attempt risk that could be translated into clinical settings to improve psychiatric care in this population. Trial registration: ClinicalTrials.gov identifier: NCT03538197, first registered on 05/29/2018. The first patient was enrolled 05/22/2018.